Ileocolonic Healing After Extended Small Bowel Resection in Mice: NOD2 Deficiency Impairs Anastomotic Healing and Postoperative Outcome. Issue 9 (8th February 2021) - Witte, Maria; Reiner, Johannes; Bannert, Karen; Jaster, Robert; Maschmeier, Christian; Schafmayer, Clemens; Lamprecht, Georg; Berlin, Peggy
Abstract: Background: Nucleotide-binding oligomerization domain-containing protein 2 ( NOD2 ) mutations are a genetic risk factor for Crohn disease. Ileocecal resection is the most often performed surgery in Crohn disease. We investigated the effect of Nod2 knockout (KO) status on anastomotic healing after extended ileocecal resection (ICR) in mice. Methods: Male C57BL6/J wild-type and Nod2 KO mice underwent an 11 cm resection of the terminal ileum including the cecum. An end-to-end jejuno-colostomy was performed. Animals were killed after 5 days investigating bursting pressure, hydroxyproline content, and expression of matrix metabolism genes, key cytokines, and histology of the anastomosis. Results: Mortality was higher in the Nod2 KO group but not because of local or septic complications. Bursting pressure was significantly reduced in the Nod2 KO mice (32.5 vs 78.0 mmHg, P < 0.0024), whereas hydroxyprolin content was equal. The amount of granulation tissue at the anastomosis was similar but more unstructured in the Nod2 KO mice. Gene expression measured by real-time polymerase chain reaction showed significantly increased expression for Collagen 1alpha and for collagen degradation as measured by matrix metalloproteinase-2, -9, and -13 in the Nod2 KO mice. Gelatinase activity from anastomotic tissue was enhanced by Nod2 status. Gene expression of arginase I, tumor necrosis factor-α, and transforming growth factor-ß but not inducible nitric oxide synthase were also increased at the anastomosis in the Nod2 KO mice compared with the control mice. Conclusions: We found that Nod2 deficiency results in significantly reduced bursting pressure after ileocecal resection. This effect is mediated via an increased matrix turnover. Patients with genetic NOD2 variations may be prone to anastomotic failure after bowel resection.